Bio-orthogonal "click-and-release" donation of caged carbonyl sulfide (COS) and hydrogen sulfide (H2S). Issue 8 (11th January 2017) - Steiger, Andrea K.; Yang, Yang; Royzen, Maksim; Pluth, Michael D.
Abstract : The inverse-electron demand Diels–Alder (IEDDA) click reaction between thiocarbamate-functionalized trans -cyclooctenes and tetrazines provides a new strategy for bio-orthogonal COS/H2 S delivery. Abstract : Hydrogen sulfide (H2 S) is an important biomolecule with high therapeutic potential. Here we leverage the inverse-electron demand Diels–Alder (IEDDA) click reaction between a thiocarbamate-functionalized trans -cyclooctene and a tetrazine to deliver carbonyl sulfide (COS), which is quickly converted to H2 S by the uniquitous enzyme carbonic anhydrase (CA), thus providing a new strategy for bio-orthogonal COS/H2 S donation.